Stability and Bifurcation of a 3D Eco Epidemiological Predator Prey Model with Pesticide - Aqiila Ollyana Savitri; Dian Savitri (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2026)
Eco–epidemiological predator–prey models provide an important mathematical framework for understanding the interaction between disease transmission, predation, and human intervention in ecological systems. This study investigates a three–dimensional deterministic model incorporating saturated disease incidence, Holling type II predation, and pesticide application. Analytical techniques are employed to determine the existence and local stability of biologically feasible equilibrium points, while numerical simulations using a fourth–order Runge–Kutta method illustrate the dynamical behavior of the system under different parameter regimes. The analysis reveals the possibility of disease–free, predator–free, and interior coexistence equilibria, as well as bistability depending on parameter values and initial conditions. Bifurcation analysis identifies critical thresholds in disease transmission and predator conversion efficiency that govern transitions between predator persistence and extinction. These findings provide theoretical insights for integrated pest management strategies by emphasizing the balance between chemical control and ecological stability.